Dupilumab Efficacy and Safety in Moderate-to-Severe Uncontrolled Asthma - Castro, Mario; Corren, Jonathan; Pavord, Ian D; Maspero, Jorge; Wenzel, Sally; Rabe, Klaus F; Busse, William W; Ford, Linda; Sher, Lawrence; FitzGerald, J. Mark; Katelaris, Constance; Tohda, Yuji; et al. (The New England journal of medicine, 2018)
Treatment of uncontrolled asthma with dupilumab, an anti–interleukin-4 and anti–interleukin-13 receptor monoclonal antibody, in addition to usual therapy, led to a rate of severe exacerbations that was approximately 50% lower than the rate with placebo.